Development of biochar using herbal industry waste for removal of hexavalent chromium from aqueous solution: Column study - Suman Pawar; Kogali Uma; Thomas Theodore (Results in Chemistry, 2024)
Biochar is an rich source of carbon formed through biomas’s thermal decomposition. There is a lot of scope of interest in developing biochar derived from biomass in various disciplines to address the most significant ecological challenges. In the present study herbal waste collected from herbal processing industry (Bangalore, India). So, this biomass will be no use after the extraction process. Hence, present work mainly concentrates the conversion this herbal waste to biochar (BC). Research highlights the BC was prepared from herbal industry waste using pyrolysis method. The obtained BC used as adsorbent for adsorption of Cr (VI) from aqueous solution. A characterization of BC was performed using XRD, SEM-EDS and FT-IR which confirms the material. The adsorption experiments were carried out using batch and fixed bed column. The experimental studies were carried out at room temperature with initial Cr (VI) concentrations (IC) of 10–120 ppm using an adsorbent dosage (AD) of 0.05–0.55 g, agitation speed of 150 rpm for contact time (CT) 15–165 min and temperature (20–40 °C). Then various parameters for column study like bed height, flow rate and IC were also studied. The maximum removal of Cr (VI) was 88 % found at a pH 2, AD 0.55g, CT 90 min, and IC 100 ppm at 30 °C. For column study: higher removal of Cr (VI) achieved by bed height (BH) of 6 cm and at lower flow rate (FR), of 3 mL/min.